Effective mathematics teaching through the appropriate usage of principles of teaching, tasks and feedback implementation among mathematics teachers (2021)
This study sought to determine the principles of teaching they consider when designing tasks for teaching, the types of tasks that address the principles being implemented and how they seek feedback on the theoretical and practical aspects of the framework by the mathematics teachers in primary, secondary, colleges of education and university in Oyo state. The study adopted a descriptive research design of correlational type to achieve the purpose of the study. A total number of two hundred (241) and forty-one mathematics teachers in Ibadan, Oyo state, Nigeria were selected as respondents. Sampling was done using stratifies sampling technique from primary, secondary and Colleges of education in Oyo State, Nigeria. The age range of respondents was 47±10.5 years with mean of 48.41 and 3.75 standard deviation. The research instrument employed was self-developed questionnaire for the purpose of data collection for the study. The questionnaire consists of demographic section, and principles of teaching that teachers across the categories of school, types of tasks that addresses the principles of teaching indicated and how feedback is obtained on the theoretical and practical aspect of the framework. The instrument was pilot tested using mathematics teachers in Ogun state teaching staff commission and the reliability coefficients obtained were 0.81, 0.63 and 0.73 for primary, secondary and college of education respectively. Data collected was analysed using using statistical tools like frequency counts, percentages and measure of central tendency (mode). The findings revealed that there were similar responses on the principles of teaching indicated by all the categories of the teachers except the university teachers. On the issue of types of tasks that address the principles indicated there was consensus in their responses, and finally, there is a wider disparity on how the mathematics teachers at various educational levels seek feedback on the theoretical and practical aspect of the framework. It was concluded that varying degree of performance of learners in mathematics at the various level of education was due to disparity in the method of seeking for feedback and to some extent the differences in the types of tasks that address the principles of teaching being claimed. Based on this, researcher recommended that standard as listed in principles of teaching should be adhere to by mathematics teachers, tasks that are commensurate with the standard of principles of teaching and the appropriate measures of feedback should be followed to the later.